(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article analyzes the activities of national equestrian games. Changes in work activity and the dynamics of riders’ movements in many types of equestrian sports are studied. It includes an analysis of the requirements and characteristics of materials for special riders’ clothing. The article also develops general requirements and requirements for materials for the production of special national equestrian clothing.